Efektivitas Penggunaan Suhu Inkubasi Terhadap Perkembangan Embrio Telur Ikan Betok (Anabas testudineus Bloch) - Suriansyah Suriansyah (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2021)
The development of fish egg embryos can be influenced by environmental factors, one of which is water temperature. This study aims to determine the effectiveness of the use of incubation temperature on the development of climbing perch fish eggs (Anabas testudineus Bloch). The benefit of this research is as a concentration of appropriate technology for the development of climbing perch fish hatchery in a sustainable manner. The effectiveness of the use of incubation temperature on the development of climbing perch fish egg embryos is that the incubation temperature of 29oC is very good for the development of climbing perch fish embryos starting from the cell division process to hatching eggs, the length of time for hatching eggs is 24 hours, the percentage rate of hatching eggs is 92% and the percentage rate the abnormality of climbing perch fish larvae is 5.43%. Keywords : Incubation temperature, development of climbing perch fish egg embryo